The Effect Of The Controversial Issues Learning Model On The Activeness In Expressing Opinions In Civic Education Learning In Grade IV Of UPT SPF SD Inpres Bontoa, Makassar City - Fatbillah, Nana; AP, Nurfaizah; Pagarra, Hamzah (International Journal of Elementary School Teacher, 2024)
The aim of this study is to determine how the implementation of the controversial issues learning model affects students' activeness in expressing opinions in civic education lessons, and how the controversial issues model influences students. This research uses a quantitative approach as the data are presented in numerical form, and it applies a quasi-experimental design of the Non-Equivalent Pre-Test Post-Test type due to the difficulty of controlling all external variables that affect the experimental process. The design uses two sample groups, with a total of sixty-four students obtained through saturation sampling, consisting of an experimental class and a control class. The research was conducted in the even semester of the 2023/2024 academic year in June. Data were collected through observation sheets and documentation. Data analysis techniques include descriptive statistical analysis, normality test, homogeneity test, and hypothesis testing. The results show that the application of the controversial issues learning model has a positive impact on students’ activeness in civic education in Grade IV of UPT SPF SD Inpres Bontoa, Tamalate District, Makassar City.